Tinjauan Fikih Muamalah Terhadap Jual Beli Bersyarat Sistem All You Can Eat : Studi Kasus Resto Matjeo Korean Grill Jember - Diana Ulfah (LP3M KH Yazid Karimullah Institute, 2021)
The implementation of the conditional sale and purchase of the all you can eat system is to pay one price according to the package menu chosen so that the buyer can enjoy all the food served as much as possible without a measure limit, but there are several requirements that must be obeyed by the buyer. The problems that arise in the sale and purchase, first, regarding the object of sale and purchase which is still unclear because the seller does not give the amount and measure to the buyer, second, with the requirements applied in the restaurant contrary to the principles of muamalah, namely freedom which can cause the buyer's rights to be absent. So the focus of research in this study is how is the practice of conditional buying and selling of the all you can eat system? and how is the muamalah fiqh review of conditional buying and selling of the all you can eat system?. The research method used in this research is a descriptive qualitative approach with the type of field research, the location of this research is located at Resto Matjeo Korean Grill Jember. The data sources used in this research are primary data and secondary data. The data collection method uses observation, documentation, and interviews, then when the data is collected it is analyzed using descriptive analysis method. In this study, it can be concluded that the conditional sale and purchase of the all you can eat system includes garar yasir, which has a little uncertainty and in Islamic law is ma'fu and cannot cancel the sale and purchase contract. Meanwhile, the conditions applied by the restaurant are included in the valid conditions, and are allowed in Islamic law, because the conditions applied are aimed at mutual benefit.